Real Time Analytics for Characterizing the Computer User's State - Carneiro, Davide; Araújo, Daniel; Pimenta, André; Novais, Paulo (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2016)
In the last years, the amount of devices that can be connected to a network grew significantly allowing to, among other tasks, collect data about the environment or the people in it in a non-intrusive way. This generated nowadays well-known topics such as Big Data or the Internet of Things. This also opened the door to the development of novel and interesting applications. In this paper we propose a distributed system for acquiring data about the users of technological devices in a non-intrusive way. We describe how this data can be collected and transformed to produce meaningful interaction features, that reveal the state of the individuals. We analyse the requirements of such a system, namely in terms of storage and speed, and describe three prototypes currently being used in three different domains of application.